The relationship between business competition and welfare in Indonesia - Maman Setiawan; Rina Indiastuti; Nury Effendi (PLoS ONE, 2025)
This research freshly investigates the effect of business competition on national welfare in Indonesia. This research uses business competition index data obtained from the Indonesia Competition Commission (KPPU) and welfare indicators data collected from the Indonesian Bureau of Central Statistics (BPS) at the economic sectoral and provincial levels for the period 2018–2020. The relationship between business competition and welfare is estimated using pooled regression model combining year, economic sector, and province. This research also uses business competition index applying both same weights for all dimensions of competition and the weights derived from principal component analysis. This research finds that business competition has a positive effect on welfare as represented by gross regional domestic product, regional productivity, productivity growth, wages, and human development index. Furthermore, the regions with high scores on the competition index mostly come from Java Island. Therefore, Indonesian government must encourage the mainstreaming of business competition in all provinces in Indonesia.